2019
DOI: 10.1016/j.ecss.2019.106268
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of tintinnid ciliates along salinity gradient in the Pearl River Estuary in southern China

Abstract: from upstream freshwaters to polyhaline waters. A total of 43 tintinnid species in 15 genera were identified. Freshwater, brackish and marine species occurred in sequence along salinity gradient. Tintinnopsis mayeri, T. tubulosa and Tintinnidium fluviatile were freshwater species. Fourteen and 15 tintinnid species were considered as brackish and marine species, respectively. The preferred salinity of freshwater species was < 3, and the abundance of freshwater species decreased along salinity gradient. Preferre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…D. ganymedes and S. steenstrupii are well-known warm water species in the Pacific, Atlantic, and Indian Oceans ( Dolan et al, 2013b ). A. minor was found in coastal ( Jyothibabu et al, 2008 ; Saab et al, 2012 ; Li et al, 2016b , 2019 ; Jung et al, 2017 ) and warm oceanic waters ( Ota and Taniguchi, 2003 ; Kim et al, 2012 ; Li et al, 2018 ). E. pacificus occurs in warm waters ( Kim et al, 2012 ; Li et al, 2016a , 2018 ), continental shelf waters ( Li et al, 2016b ; Yu et al, 2016 ), and the region of the Kuroshio and Oyashio Currents ( Gómez, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…D. ganymedes and S. steenstrupii are well-known warm water species in the Pacific, Atlantic, and Indian Oceans ( Dolan et al, 2013b ). A. minor was found in coastal ( Jyothibabu et al, 2008 ; Saab et al, 2012 ; Li et al, 2016b , 2019 ; Jung et al, 2017 ) and warm oceanic waters ( Ota and Taniguchi, 2003 ; Kim et al, 2012 ; Li et al, 2018 ). E. pacificus occurs in warm waters ( Kim et al, 2012 ; Li et al, 2016a , 2018 ), continental shelf waters ( Li et al, 2016b ; Yu et al, 2016 ), and the region of the Kuroshio and Oyashio Currents ( Gómez, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…As with HPs, the realized niche of viruses would be confined by salinity, as salt stress has been shown to directly affect their survival and ability to infect (Wei et al, 2019). Ciliates appeared to be less salinity-sensitive than HPs and viruses because they expanded across a wide range of salinities (Li et al, 2018(Li et al, , 2019. However, due to a lack of data on nanoflagellates and copepods, which are commonly acknowledged as the food and grazers of ciliates, it was unknown whether nanoflagellates and copepods affected ciliate abundance, biomass, and community composition in the Jiulong River estuary during a short period.…”
Section: Environmental Factors Shaping the Abundance Biomass And Comm...mentioning
confidence: 99%
“…According to Hada (1974), the species was found at a water temperature of about 29.1-29.5 • C, a salinity of about 28.38-33.26 , and a pH of about 7.9-8, which were basically closed to the environmental factors in our study (salinity 27 , pH 8.1, and water temperature 23.5 • C). In Li et al (2019), L. nordqvisti was considered as a brackish species, occurring at a salinity range of 9.2-34.1 . During winter and early spring, the abundance of L. nordqvisti was higher in Kuwait waters (Yousif Al-Yamani et al, 2011).…”
Section: Occurrence and Ecology Of Leprotintinnus Nordqvistimentioning
confidence: 99%
“…In the study of Li et al (2019), L. simplex was considered as a brackish species, occurring at a salinity range of 11.8-34.1 . A 10-year (May 2003 to December 2012) survey in Jiaozhou Bay, found that the species excluding May were present with a maximum abundance of 130 ind/L (Feng et al, 2018).…”
Section: Occurrence and Ecology Of Leprotintinnus Simplexmentioning
confidence: 99%